The Influence of Social Media on the Culture of Saying Islamic Greetings in Mtsn 1 Banda Aceh Students - Ariny Salsabila Qamari; Nurmahni Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Nowadays, technology has become a daily necessity. With the development of time and technology, new terms of greeting have begun to emerge. However, what is feared is the fading of the existence of the culture of greeting in Islam, namely, Assalamu'alaikum. This concern is caused by other greetings that tend to be considered more contemporary. Meanwhile, greetings are also included in the identity of an Islamic believer. This study aims to determine the effect of social media development on the culture of greetings in Islam and was conducted at MTsN 1 Model Banda Aceh with a sample of 20 students in class VIII-1. The method used is qualitative, through questionnaire interviews in the form of a Google Form. The results showed the highest percentage of 96% that students in class VIII-1 tended to answer greetings more often from their friends who greeted them, namely Assalamu'alaikum, which can be concluded that self-awareness and initiative owned by them to say greetings were still quite lacking. Meanwhile, the lowest percentage of 72% shows that there are still many content creators who have not implemented greetings in their content.